Galectin-1-mediated expression of proteins-regulators of cell cycle and growth factors in gastric cancer - Yu. V. Kolobovnikova; A. I. Dmitrieva; K. I. Jankovic; O. A. Vasilyeva; I. L. Purlik; V. V. Novitskiy; O. I. Urazova; S. A. Hardikova (Бюллетень сибирской медицины)
The purpose of the study was to analyze the expression of proteins-regulators of the cell cycle (p53 and p21) and receptors for endothelial (VEGFR) and epidermal (EGFR) growth factors depending on the expression of galectin-1 in tumor cells in gastric cancer.Materials and methods. 52 patients with diagnosis of gastric cancer were examined. We used the tissue samples of malignant neoplasms of the stomach, which were obtained during surgical intervention. In tumor tissue the expression of galectin-1, p53 and p21 proteins, and receptors of VEGF and EGF were evaluated by immunohistochemistry. The obtained results were analyzed by statistical methods.Results. It is shown that in patients with gastric cancer accompanied by overexpression of galectin-1, high expression of mutant protein p53 and EGFR in tumor tissue was recorded significantly more frequently. Low expression of VEGFR was observed in all patients with gastric cancer regardless of the level of expression of galectin-1 by tumor cells. Association of galectin-1 expression with expression of protein p53 and EGF receptor by stomach tumor cells was set.Conclusion. The relationship between overexpression of galectin-1 and overexpression of mutant p53 protein (not showing antioncogenic properties) and receptor for epidermal growth factor (EGFR) by stomach tumor cells is a negative prognostic criterion of the neoplastic process in gastric cancer.